The Code Switching of Singkil Language in Indonesian Language Learning Process at Junior High School of Aceh Singkil and Its Usefulness as Student Reading Material - M. Khairunsyah; Abdurahman Adisaputera; Marice Marice (BIRCU, 2020)
In teaching learning process at SMP Darulmuta'alimin Tanah Merah Aceh Singkil, code switching and code mixing are useful in some events. This does not only happen to students, but also teachers who have the same background (mother tongue) as students. A teacher at SMP Darulmuta'alimin Tanah Merah Aceh Singkil uses the local language or mother tongues so that the students are being taught understand. In accordance with the explanation of Article 36, Chapter XV, of the 1945 Constitution, it can be seen that the language of instruction is used in the teaching and learning process in the Indonesian class. This type of research is qualitative analytical descriptive, which seeks to describe the characteristics of the data in accordance with the actual situation. The description is described as it is systematically, factually, and accurately regarding the data and characteristics of the phenomena under study. The data shows that the code switching event in Indonesian language learning in grade VII-A SMP Darulmuta'alimin Tanah Merah Aceh Singkil, which is from the Singkil language to Indonesian. Since the beginning of the conversation in the learning process, the teacher and students communicate using Singkil and the end of their conversation using Indonesian.